Public Expenditure on Education : A Review of Selected Issues and Evidence - Anit N. Mukherjee
The role of education in economic development has been recognised for quite some time in mainstream economic literature. Divergence between the private and social rate of return from education is the rationale for intervention by the state in ensuring equity in opportunity across the population. The so-called `New Growth Theories' predict that higher levels of schooling and better quality of workforce will lead to an increase in the rate of growth, further strengthening the case for public expenditure on education. The outcome of these lines of research also has implications for the financing of education. However, the effectiveness and efficiency of resource allocation by the governmenthas generated considerable debate, both from ideological and technical points of view. It is widely acknowledged that there is a large scope for improvement in both the level, and the quality of publicly-funded education. New institutional arrangements are being designed to address the deficiencies in incentives and monitoring, thereby improving quality.